Cardio-visual full body illusion alters bodily self-consciousness and tactile processing in somatosensory cortex - Heydrich, Lukas (Sci Rep, 2018)
Prominent theories highlight the importance of bodily perception for self-consciousness, but it is currently not known whether this is based on interoceptive or exteroceptive signals or on integrated signals from these anatomically distinct systems, nor where in the brain such integration might occur. To investigate this, we measured brain activity during the recently described ‘cardio-visual full body illusion’ which combines interoceptive and exteroceptive signals, by providing participants with visual exteroceptive information about their heartbeat in the form of a periodically illuminated silhouette outlining a video image of the participant’s body and flashing in synchrony with their heartbeat. We found, as also reported previously, that synchronous cardio-visual signals increased self-identification with the virtual body. Here we further investigated whether experimental changes in self-consciousness during this illusion are accompanied by activity changes in somatosensory cortex by recording somatosensory evoked potentials (SEPs). We show that a late somatosensory evoked potential component (P45) reflects the illusory self-identification with a virtual body. These data demonstrate that interoceptive and exteroceptive signals can be combined to modulate activity in parietal somatosensory cortex.